Graphene composite heating film with chloride ion blocking capability and preparation method and application thereof
By introducing a multi-layer composite structure of layered bimetal hydroxide (LDH) into the graphene composite heating film, the corrosion problem of existing films in chlorine-containing environments is solved, and higher mechanical properties and stability are achieved, and it is suitable for a variety of cold environment applications.
Patent Information
- Application Number
- CN202411645467.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing graphene composite heating films are prone to corrosion when exposed to chlorine-containing environment for a long time, which affects the heating performance and service life. The substrate has high brittleness or insufficient mechanical strength, making it difficult to maintain good mechanical properties under bending or external forces.
Laminated bimetallic hydroxide (LDH) with unique layered structure and ion exchange capability is introduced to form a multi-layer composite structure, which acts as a chloride ion barrier layer, and combines with a graphene heating layer to enhance the durability and stability of the film.
Effectively block chloride ion corrosion, enhance the mechanical properties and stability of composite membranes, ensure good performance in corrosive environments for a long time, and is suitable for marine equipment, chemical equipment and building structures in cold environments.
Smart Images

Figure CN119653526A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite films, and in particular relates to a graphene composite heating film with chloride ion barrier capability, a preparation method thereof, and an application of the graphene composite heating film in the preparation of ice and snow melting materials. Background Art
[0002] In cold regions such as Heilongjiang, graphene heating film can be used as an alternative or auxiliary technology to chloride salt snow melting technology, reducing the use of chloride salt, thereby reducing environmental pollution and the risk of corrosion of infrastructure. The graphene heating film generates heat after being powered on, which can effectively melt snow and ice on the surface of roads, bridges and buildings. Compared with traditional heating systems, graphene heating film has the advantages of fast response speed, uniform heating and low energy consumption. The chemical stability and good shielding properties of graphene enable it to effectively block the intrusion of chloride ions when exposed to chloride salt environments, reducing corrosion to infrastructure. At the same time, graphene heating film can reduce dependence on chloride salts, thereby reducing environmental pollution, and the high durability and corrosion resistance of graphene heating film give it significant advantages in long-term use, reducing maintenance costs and frequency.
[0003] However, existing graphene composite heating films, especially those composited with metal materials or conductive polymers, are usually susceptible to corrosion when exposed to chlorine-containing environments for a long time, affecting heating performance and service life. In addition, existing graphene composite films are difficult to maintain good mechanical properties under bending or external forces due to the brittleness of the substrate or insufficient mechanical strength. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a graphene composite heating film with chloride ion blocking ability, a preparation method thereof and an application in the preparation of ice and snow melting materials. By introducing a layered double metal hydroxide (LDH) with a unique layered structure and ion exchange capacity, it can effectively block the penetration of corrosive ions such as chloride ions, solve the problem of insufficient corrosion resistance of similar composite membranes, and enhance the durability and stability of the composite membrane.
[0005] To achieve the above purpose, the solution adopted by the present invention is as follows:
[0006] In the first aspect, the present invention provides a graphene composite heating film with chloride ion blocking capability, comprising a graphene heating layer and a chloride ion blocking layer, wherein the chloride ion blocking layer is a multilayer composite structure, and each layer of the composite structure is composed of alternating layers consisting of a layered double hydroxide (LDH) and a graphene layer intercalated between the layered double hydroxides (LDH).
[0007] Preferably, the layered double metal hydroxide (LDH) is selected from one or more of magnesium aluminum layered double metal hydroxide, zinc aluminum layered double metal hydroxide, cobalt aluminum layered double metal hydroxide, nickel aluminum layered double metal hydroxide, titanium aluminum layered double metal hydroxide, zinc iron layered double metal hydroxide and copper aluminum layered double metal hydroxide, preferably magnesium aluminum layered double metal hydroxide.
[0008] Preferably, anionic carbonate ions (CO3 2- ) and / or sulfate ions (SO4 2- ).
[0009] Preferably, the molar ratio of metal ions in the layered double hydroxide (LDH) is 2+ / M 3+ =(1-5):1, preferably 2:1 or 3:1.
[0010] Preferably, the material of the graphene heating layer is modified graphene, preferably chemically reduced modified graphene oxide (rGO).
[0011] Preferably, the thickness of the graphene heating layer is 50-500 nm, and the thickness of the chloride ion barrier layer is 100-1000 nm.
[0012] In a second aspect, the present invention further provides a method for preparing the graphene composite heating film having chloride ion barrier capability as described above, comprising the following steps:
[0013] Modifying the graphene heating layer of the substrate layer to form a graphene heating layer;
[0014] Preparation of layered double hydroxides (LDH) and LDH-graphene composites having graphene layers intercalated between the layered double hydroxides (LDH);
[0015] forming a multilayer LDH-graphene composite film as a chloride ion barrier layer on the substrate layer of the modified graphene heating layer;
[0016] Hot pressing is performed to form a graphene composite heating film with chloride ion barrier capability.
[0017] Preferably, the LDH-graphene composite material is prepared by a solution coprecipitation method, and during the coprecipitation reaction, the pH value of the reaction solution is between 8.5-10.5, and the reaction temperature is in the range of 25°C-80°C; wherein, in the formed LDH-graphene composite material, an alternating layer structure consisting of a layered double metal hydroxide (LDH) and a graphene layer intercalated between the layered double metal hydroxides (LDH) is formed, the total number of layers is between 10-100 layers, and the thickness ratio of the LDH and graphene layers is (1-5):1, preferably (1-2):1.
[0018] Preferably, in the step of forming a multilayer LDH-graphene composite material on the base layer of the modified graphene heating layer, the LDH-graphene composite material is uniformly coated on the graphene heating layer by coating, solution impregnation, layer-by-layer assembly, sol-gel, chemical vapor deposition (CVD) or spray drying, and a multilayer composite layer composed of the LDH-graphene composite material is formed on the graphene heating layer.
[0019] In a third aspect, the present invention also provides a graphene composite heating film with chloride ion barrier capability as described above and a use of the graphene composite heating film with chloride ion barrier capability prepared by the preparation method as described above in the preparation of ice and snow melting materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The graphene composite heating film with chloride ion blocking capability provided by the present invention has an introduced layered double hydroxide (LDH), which not only acts as a chloride ion barrier in the composite film, but also has the characteristics of ion regulation, high thermal stability, adjustable electrical conductivity, etc., and also provides additional mechanical strength. At the same time, graphene gives the composite film good flexibility as well as excellent electrical conductivity and thermal conductivity, ensuring efficient electric heating performance. The combination of the two enhances the mechanical properties of the composite film, which can be used as a heating film and can shield chloride ions, so that it can maintain good performance for a long time in a corrosive environment. It is particularly suitable for fields that require efficient blocking of chloride ion corrosion and serve in cold environments, such as marine equipment, chemical equipment, and building structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the cross-sectional structure of the graphene composite heating film involved in the present invention.
[0023] Figure 2 It is a schematic diagram of the interlayer internal structure of the graphene composite heating film involved in the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.
[0025] like Figure 1 , Figure 2 As shown, the present invention provides a graphene composite heating film with chloride ion blocking capability, comprising a graphene heating layer 1 and a chloride ion blocking layer 2, wherein the chloride ion blocking layer 2 is a multi-layer composite structure, each of which is composed of alternating layers of layered double metal hydroxides (LDH) and graphene layers intercalated between the layered double metal hydroxides (LDH). Among them, the graphene heating layer 1 provides good electrical and thermal conductivity, and the chloride ion blocking layer 2 comprising the layered double metal hydroxide (LDH) serves as a chloride ion capture and neutralization layer, thereby achieving an effective chloride ion blocking function.
[0026] In the graphene composite heating film with chloride ion barrier capability of the present invention, the graphene heating layer 1 is a base layer material, and graphene material or modified graphene material is used. The graphene material has excellent electrical conductivity and thermal conductivity, and can achieve rapid heating at a lower voltage, and realize efficient electric heat conversion. Therefore, using graphene material as the thermal conductive layer of the graphene composite heating film can ensure the electric heating performance of the graphene composite heating film.
[0027] As a preferred embodiment of the present invention, the graphene heating layer 1 adopts modified graphene material, for example, graphene oxide (rGO) modified by chemical reduction, so as to enhance the bonding force between it and the layered double hydroxide (LDH) in the chloride ion barrier layer 2.
[0028] In some embodiments of the present invention, the surface modification of graphene by chemical reduction can be performed according to conventional modification methods. For example, graphene oxide (GO) can be reduced to reduced graphene oxide (rGO) by chemical reduction modification, which can maintain the conductivity and chemical activity of graphene. Specifically, the following steps are included:
[0029] (1) dispersing graphene oxide in water and ultrasonically dispersing to form a stable suspension;
[0030] (2) adding a reducing agent and performing a reduction reaction at a temperature of 80° C. to 100° C. for a reaction time of 6 to 24 hours, until the color of the solution changes from brown to black, and the surface graphene oxide is reduced to reduced graphene oxide (rGO);
[0031] (3) The reduced graphene oxide (rGO) is filtered and washed to remove the unreacted reducing agent, and then dried to obtain reduced graphene oxide powder.
[0032] In the above step (2), the reducing agent used is, for example, hydrazine hydrate (N2H4·H2O) or ascorbic acid (vitamin C). Among them, hydrazine hydrate (N2H4·H2O) is a strong reducing agent that can effectively reduce graphene oxide to generate reduced graphene oxide (rGO) with better conductivity; ascorbic acid (vitamin C) is a mild reducing agent that can partially reduce the oxidized groups on the surface of graphene oxide, but will retain a certain hydrophilicity.
[0033] The above step (2) can also be reduced by hydrogen, that is, the graphene oxide is exposed to a hydrogen flow and reduced at a high temperature (usually 200-300° C.).
[0034] In the graphene composite heating film with chloride ion barrier capability of the present invention, the main material of the chloride ion barrier layer 2 is layered double metal hydroxide (LDH), including but not limited to magnesium aluminum layered double metal hydroxide, zinc aluminum layered double metal hydroxide, cobalt aluminum layered double metal hydroxide, nickel aluminum layered double metal hydroxide, titanium aluminum layered double metal hydroxide, zinc iron layered double metal hydroxide, copper aluminum layered double metal hydroxide, etc. These layered double metal hydroxides (LDH) have a layered structure and good ion exchange performance, and can capture and neutralize chloride ions, thereby preventing chloride ions from corroding the graphene substrate material.
[0035] in:
[0036] Magnesium aluminum layered double hydroxide (Mg-Al LDH): It has good ion exchange capacity, can adsorb harmful ions, improve the durability of materials, and when combined with other materials (such as graphene), it can improve the mechanical strength and thermal stability of the composite material.
[0037] Zinc-aluminum layered double hydroxide (Zn-Al LDH): It can effectively block chloride ion penetration and provide excellent anti-corrosion protection. It is particularly suitable for humid and corrosive environments. It also has certain antibacterial properties and is suitable for medical and hygiene-related applications.
[0038] Cobalt aluminum layered double hydroxide (Co-Al LDH): has good chloride ion barrier properties and is widely used in corrosion protection.
[0039] Nickel aluminum layered double hydroxide (Ni-Al LDH): It has a strong barrier effect on chloride ions and is often used in anti-corrosion coatings.
[0040] Titanium-aluminum layered double hydroxide (Ti-Al LDH): Because titanium has good corrosion resistance, this type of LDH can enhance the material's shielding ability against chloride ions.
[0041] Zinc-iron layered double hydroxide (Zn-Fe LDH): It has both the anti-corrosion properties of zinc and the physical stability of iron, and can effectively prevent chloride ion penetration.
[0042] Copper-aluminum layered double hydroxide (Cu-Al LDH): Copper has antimicrobial properties and combined with aluminum can provide a shield against chloride ions.
[0043] In some embodiments, the double hydroxide (LDH) having a layered structure may have anions intercalated between the layers, such as anions carbonate ions (CO3 2- ) or sulfate ion (SO4 2- ), these ions can be inserted into layered double hydroxides (LDHs) via electrostatic adsorption or interfacial reactions.
[0044] Among them, electrostatic adsorption is the main method of anion insertion. LDH has positive charges in its layered structure, and carbonate (CO3 2- ), sulfate (SO4 2- ) and other anions are negatively charged and can be naturally inserted into the interlayers through electrostatic interactions, that is, by dispersing the layered double hydroxide (LDH) in a solution containing carbonate or sulfate, these anions can be naturally adsorbed to the metal cations (such as magnesium and aluminum) between the layered double hydroxide (LDH) layers through electrostatic interactions.
[0045] The interfacial reaction method is to disperse the layered double hydroxide (LDH) in a carbonate (CO3 2- ) or sulfate (SO4 2- ) solution, the intercalation process can be affected by controlling the pH value and temperature of the solution. For example, controlling the pH value between 8.5 and 10.5 can promote the formation of carbonate (CO3 2- ) or sulfate (SO4 2- ) during the intercalation process, appropriately increasing the temperature (25-80°C) can accelerate the diffusion of anions and improve the intercalation efficiency.
[0046] Through the above steps, anions carbonate ions (CO3 2- ) or sulfate ion (SO4 2- ), in the intercalated carbonate ion (CO3 2- ), the interlayer spacing is The intercalated sulfate ion (SO4 2- ), the interlayer spacing is The introduction of these two anions is suitable for the chloride ion barrier requirements under different conditions. The smaller the interlayer spacing, the stronger the chloride ion barrier effect.
[0047] At the same time, the anion carbonate ion (CO3 2- ) or sulfate ion (SO4 2- ) will also affect the interlayer spacing. When the insertion amount is small, the interlayer spacing is small and the chloride ion barrier effect is strong. However, if too much is inserted, the stability of the layered structure may be destroyed and the performance of the composite membrane material may be reduced. Therefore, the insertion amount is generally controlled within the range of 1-2 mol anion / mol LDH to ensure interlayer stability and barrier effect.
[0048] In some embodiments, auxiliary materials may be introduced into the layered double hydroxide (LDH) according to actual needs to further enhance the performance of the composite membrane, such as electrical conductivity, mechanical strength and thermal stability, without significantly weakening the chloride ion barrier capability. The auxiliary materials include but are not limited to:
[0049] (1) Polymer:
[0050] Function: Conductive polymers (such as polypyrrole, polyaniline) or insulating polymers (such as polyethylene, polyurethane) can be introduced to enhance flexibility, corrosion resistance or other physical properties;
[0051] Technical impact: The addition of polymers may slightly affect the chloride ion barrier effect of the composite membrane, depending on the structure and properties of the polymer; conductive polymers can maintain conductivity, while insulating polymers may reduce conductivity but improve flexibility and corrosion resistance.
[0052] (2) Silicate nanoparticles:
[0053] Function: Silicate nanoparticles can be used as fillers to enhance the mechanical strength, heat resistance and corrosion resistance of composite films;
[0054] Technological impact: The introduction of silicate nanoparticles can improve the structural stability of the composite membranes and enhance the chloride ion shielding ability because their nanoscale structure helps to block ion penetration.
[0055] (3) Transition metal oxides (such as TiO2, ZnO):
[0056] Function: Transition metal oxides have excellent corrosion resistance and photocatalytic properties, which can enhance the corrosion resistance and photocatalytic protection ability of the composite film;
[0057] Technical impact: Materials such as TiO2 and ZnO will not significantly affect the chloride ion barrier effect, but will improve the corrosion resistance and self-cleaning performance of the composite film in harsh environments.
[0058] In the graphene composite heating film with chloride ion barrier capability of the present invention, layered double hydroxide (LDH) can be compounded with graphene to form a denser barrier layer, which can effectively block the corrosion of chloride ions.
[0059] The LDH-graphene composite material can be prepared by a solution co-precipitation method. The preparation of a magnesium-aluminum layered double hydroxide (Mg-Al LDH)-graphene composite material is taken as an example to illustrate this case, which specifically includes the following steps:
[0060] (1) Prepare metal salt solution:
[0061] 1.1. Select appropriate metal salts, such as magnesium salts (Mg(NO3)2, MgCl2, etc.) and aluminum salts (Al(NO3)3, AlCl3, etc.);
[0062] 1.2. Prepare magnesium salt and aluminum salt solutions of a certain molar concentration (such as 0.1M or 0.5M), where the molar ratio of magnesium to aluminum is (1-5):1, i.e. [Mg 2+ ] / [Al 3+ ]=(1-5):1, for example 2:1, 3:1, 4:1, more preferably 2:1 or 3:1, the ratio directly affects the formation of the layered structure and the chloride ion barrier ability; the concentration of the metal salt solution should be controlled in the range of 0.05M-0.5M, too high a concentration may lead to too fast precipitation, affecting the uniformity and quality of the crystal;
[0063] (2) Prepare carbonate or sulfate intercalation anion solution:
[0064] 2.1. Select an anion source such as sodium carbonate (Na2CO3) or sodium sulfate (Na2SO4) and prepare a solution of appropriate concentration (such as 0.1M) to ensure that the anion is inserted into the interlayer of LDH during the precipitation process;
[0065] (3) Preparation of graphene dispersion:
[0066] 3.1. Using graphene oxide (GO) as a precursor, dispersing it in water or ethanol, and performing ultrasonic dispersion treatment to ensure the formation of a stable graphene oxide dispersion;
[0067] 3.2. The concentration of the dispersion is generally 1-5 mg / mL to ensure that graphene is evenly distributed in LDH;
[0068] (4) placing the metal salt solution in a reaction vessel, stirring continuously with a stirrer, and slowly adding a precipitant (such as NaOH or NH4OH) at the same time, with the drop rate controlled at a few drops per minute to 1 mL per minute. Too fast a drop rate will result in uneven size of the generated precipitate particles, and the pH value of the reaction solution is controlled between 8.5 and 10.5, which is conducive to the formation of metal hydroxide precipitation and prevents excessive hydrolysis of metal ions. The temperature of the reaction vessel is controlled within the range of 25°C to 80°C as the reaction temperature of the coprecipitation reaction. A higher temperature helps to improve the precipitation rate and crystallization quality. If a higher crystallinity LDH is required, a higher temperature can be selected. For example, by controlling the reaction temperature at about 50°C, a more ordered LDH crystal structure arrangement can be obtained, which is conducive to enhancing the overall strength and stability of the composite membrane;
[0069] (5) Add sodium carbonate or sodium sulfate solution dropwise to the metal salt solution, keep stirring continuously to ensure that the anions are evenly dispersed in the reaction system. The carbonate or sulfate anions react with the metal ions to form LDH precipitates, which are inserted into the LDH interlayer by electrostatic adsorption. After the metal salt solution reacts with the anions, a white or light-colored precipitate gradually appears, which is the initial formation of LDH. Continue stirring to keep the reaction stable. The reaction time is usually 1-4 hours;
[0070] (6) During the co-precipitation process, a graphene dispersion is gradually added. The graphene will be co-precipitated with the LDH during the reaction. The amount of graphene added is usually 1-5% of the molar number of the metal ions to ensure that the graphene layers are reasonably distributed between the LDH layers, enhance the conductivity and mechanical strength of the material, and by controlling the addition time of the graphene, an alternating layer structure consisting of a layered double hydroxide (LDH) and a graphene layer intercalated between the layered double hydroxides (LDH) can be formed;
[0071] During the entire coprecipitation reaction process, the reaction time is set to 1-24h. Too short a time may lead to incomplete crystallization, while too long a time may cause the particles to grow, affecting the nanostructure and performance of the material. The stirring speed and uniformity are also crucial. Using a stirring speed of 300-800rpm can ensure uniform mixing during the precipitation process and avoid particle aggregation.
[0072] After the coprecipitation reaction is completed, the LDH-graphene composite precipitate needs to be aged, such as aging at room temperature or 60°C for 12-24 hours to improve the crystallinity and stability of the material;
[0073] (7) After the reaction is completed, the LDH-graphene composite precipitate is separated from the solution by vacuum filtration or centrifugation, and the precipitate is repeatedly washed with deionized water to remove unreacted ions and impurities, and then the obtained precipitate is dried in an oven at 60° C. to 100° C. for 12 to 24 hours to form a dry LDH-graphene composite material powder.
[0074] The solution coprecipitation method adjusts the concentration of metal ions and anions in the solution, and forms an alternating layer structure consisting of layered double hydroxides (LDH) and graphene layers intercalated between layered double hydroxides (LDH) under controlled pH conditions. The formation of LDH depends on the hydrolysis reaction of metal cations in the solution, and anions enter the LDH interlayer through adsorption and intercalation.
[0075] In order to ensure the uniformity of each layer of the composite membrane formed subsequently, the solution concentration, temperature, pH value and other conditions need to be precisely controlled. In the alternating layer structure formed, the thickness ratio of the LDH and graphene layers will affect the performance of the final composite membrane. The thickness ratio of the LDH and graphene layers is controlled between 1:1 and 2:1, which can ensure both good electrical heating performance and efficient chloride ion barrier effect.
[0076] In the alternating layer structure formed, the number of layers of the alternating layer structure should be determined according to the final application of the composite film. More alternating layers can increase the barrier capacity of chloride ions, but it will also increase the thickness of the composite film, affecting its conductivity and flexibility. Usually controlled within a few dozen layers, a good balance can be achieved between barrier properties and other properties.
[0077] The number of alternating layers is mainly determined based on the final application requirements and performance balance of the composite membrane, including the following aspects:
[0078] 1. Chloride ion barrier capacity requirements: If the risk of chloride ion corrosion in the application scenario is high (such as marine engineering, bridges, tunnels, etc.), more layers are required to enhance the barrier performance; the more layers there are, the more complex the barrier path, thereby increasing the diffusion resistance of chloride ions.
[0079] 2. Conductivity and flexibility requirements: Conductivity and flexibility are inversely proportional to the number of layers. Fewer layers help maintain conductivity and flexibility, which is very important for automotive antifreeze systems or smart building applications.
[0080] 3. Total thickness limit: The number of layers that can be accommodated needs to be calculated based on the specific thickness limit of the membrane (such as it cannot exceed a certain value to meet the flexibility requirements).
[0081] 4. Experimental optimization: Through experimental testing, the barrier performance, conductivity, flexibility and other indicators are measured under different number of layers, and the range of layers with the best comprehensive performance is selected.
[0082] Therefore, alternating layers consisting of layered double hydroxides (LDHs) and graphene layers intercalated between the layered double hydroxides (LDHs) are formed, and the number of layers is controlled within tens of layers, so that a balance between barrier properties and other properties can be achieved.
[0083] The control parameters for the number of alternating layers include:
[0084] 1. Deposition times:
[0085] (1) Adjustment method: Each deposition process forms a set of alternating layers, and the number of layers can be changed by controlling the number of deposition cycles.
[0086] (2) Impact: Increasing the number of depositions directly increases the number of layers, but its cumulative effect on the total thickness needs to be controlled.
[0087] 2. Thickness of single layer material:
[0088] (1) Adjustment method: Adjusting solution concentration: Increasing the concentration of graphene or LDH precursor solution will increase the monolayer thickness and reduce the number of layers required; Adjusting deposition time: Prolonging the time of each deposition can increase the monolayer thickness.
[0089] (2) Impact: Thin monolayers are more suitable for barrier structures that require a high number of layers, while thick monolayers are suitable for reducing the number of layers to optimize conductivity and flexibility.
[0090] 3. Properties of the basal layer:
[0091] (1) Adjustment method: By changing the roughness of the substrate surface or chemically modifying it, the adsorption and stacking efficiency of the material can be affected.
[0092] (2) Influence: The base layer affects the uniformity and density of material deposition, thereby indirectly controlling the number of layers.
[0093] 4. Assembly process parameters:
[0094] (1) Adjustment method: Control the bonding strength and thickness between layers by changing the deposition temperature, pH value or reaction time; use different assembly methods such as electrostatic adsorption and chemical bonding to change the interlayer spacing or interlayer stacking method.
[0095] (2) Influence: Process parameters can fine-tune the coverage and thickness of a single layer of material and affect the final number of layers.
[0096] 5. Ratio of LDH-graphene composite material:
[0097] (1) Adjustment method: Optimize the ratio of graphene to LDH and change the efficiency of alternating stacking of the two.
[0098] (2) Impact: High graphene content tends to reduce the number of layers (maintaining conductivity), while high LDH content tends to increase the number of layers (improving barrier properties).
[0099] In the graphene composite heating film with chloride ion barrier capability of the present invention, the chloride ion barrier layer 2 is formed by depositing the LDH-graphene composite material prepared by the above steps layer by layer on the base layer of the modified graphene heating layer to form a multilayer LDH-graphene composite film, and the layer-by-layer deposition method includes but is not limited to coating method, solution impregnation method, layer-by-layer self-assembly method, sol-gel method, chemical vapor deposition method (CVD), spray drying method, etc.
[0100] Taking the coating method as an example, the specific steps include:
[0101] (1) redispersing the dried LDH-graphene composite powder in a suitable solvent (such as water or ethanol) and treating it with ultrasound to form a uniform suspension;
[0102] (2) using a spin coating method, a drop casting method or a spray coating method to uniformly coat the LDH-graphene composite material on the base layer of the modified graphene heating layer to form a multilayer composite film;
[0103] If a thicker film is needed, the thickness of the film can be gradually increased by repeated coating;
[0104] Coating can also be performed under vacuum, for example, the vacuum degree is maintained at 10-20Pa, and the coating speed is controlled at 0.1-1.0m / s. Vacuum coating can improve the compactness of the multi-layer composite film, reduce the generation of bubbles, and help to evenly distribute the materials of each layer, especially in large-area preparation. The effect is more significant. The vacuum degree and coating speed have a direct impact on the uniformity and thickness of the layer;
[0105] (3) After coating, the multilayer composite film is heat treated at 100°C-150°C to improve the density and mechanical strength of the film and ensure a closer interlayer bonding between LDH and graphene.
[0106] Heat treatment is an important step after deposition, which directly affects the bonding strength between material layers and the physical properties of the composite film. The heat treatment temperature determines the evaporation rate of the solvent and the degree of curing of the film layer. If the heat treatment temperature is too high, it may cause cracking or thermal degradation of the material layer; if the temperature is too low, it may cause solvent residue, affecting the subsequent hot pressing effect. The heat treatment time determines the degree of curing of the material. If the time is too short, the film layer may not be completely dried and cured, affecting its mechanical properties; if the time is too long, it may cause material aging. The heat treatment time is controlled between 30 minutes and 2 hours, and is adjusted according to the thickness of the composite film and the evaporation rate of the solvent.
[0107] Taking the solution impregnation method as an example, the specific steps include:
[0108] 1. Preparation of base layer:
[0109] (1) Cleaning the substrate: Use deionized water, ethanol or other solvents to ultrasonically clean the substrate to ensure that the surface is clean.
[0110] (2) Surface treatment: hydrophilic or other chemical modifications (such as plasma treatment or acid / base treatment) are made to the substrate layer to improve the adhesion of the material; ensure that the surface of the substrate layer is uniform and flat to facilitate uniform deposition of the film.
[0111] 2. Prepare the impregnation solution:
[0112] (1) Graphene dispersion: Graphene is uniformly dispersed in water or other solvents using physical or chemical methods, and an appropriate amount of dispersant (such as a surfactant or polymer) is added.
[0113] (2) LDH precursor solution: usually an aqueous solution containing a metal ion precursor (such as Mg2+, Al3+ or Zn2+, Al3+); prepared according to the desired LDH type and stoichiometric ratio; adjusted to a pH range suitable for LDH growth (usually an alkaline environment, pH 8-12).
[0114] 3. Impregnation process:
[0115] (1) First layer immersion (e.g., graphene layer): Immerse the substrate in the graphene dispersion for a certain period of time to ensure uniform surface adsorption or attachment; the immersion time depends on the solution concentration and the required single layer thickness, usually a few seconds to a few minutes; lift the substrate, gently shake off the excess solution, and dry it naturally or use low-temperature drying.
[0116] (2) Second layer immersion (such as LDH layer): The dried substrate is transferred to the LDH precursor solution; a uniform LDH film is deposited by reaction, and the reaction time depends on the solution conditions, usually a few minutes to more than ten minutes; after lifting the substrate, it is cleaned to remove the unreacted solution and dried.
[0117] 4. Alternate dipping:
[0118] The dipping process of graphene and LDH solution was repeated to form an alternating layer structure.
[0119] 5. Post-processing:
[0120] (1) Heat treatment: low-temperature drying or high-temperature sintering at a certain temperature to enhance the interlayer bonding strength.
[0121] (2) Surface inspection: Use a microscope or other characterization methods to check the uniformity and thickness of the film.
[0122] Key parameters of solution impregnation method:
[0123] 1. Immersion time: The longer the time, the more deposition, but it may lead to uneven layer thickness or particle accumulation.
[0124] 2. Solution concentration: The higher the concentration, the higher the deposition efficiency, but too high a concentration may lead to aggregation or larger particle size.
[0125] 3. Solution pH: The deposition of LDH, in particular, is sensitive to pH and usually requires an alkaline environment to form a good layered structure.
[0126] 4. Reaction temperature: Increasing the temperature can accelerate the deposition process, but it is necessary to avoid destroying the layered structure of the material.
[0127] Advantages and applicability of solution impregnation method:
[0128] 1. Advantages: simple operation, low equipment requirements, suitable for large-area film preparation; single-layer thickness and uniformity can be controlled.
[0129] 2. Applicability: Suitable for the preparation of various composite films (such as graphene / LDH, oxide / polymer, etc.); widely used in marine engineering, automotive anti-corrosion coatings and intelligent buildings.
[0130] Layer-by-layer self-assembly method: Utilizing non-covalent forces such as charge interaction and hydrogen bonding, a multilayer structure is constructed on the substrate through repeated adsorption and washing processes. This method can achieve high-precision film thickness control and can adjust the physical and chemical properties of the composite membrane.
[0131] Sol-gel method: Through the sol-gel reaction, materials such as graphene and LDH are prepared into nanocomposite films. This method is easy to control the thickness and uniformity of the film, and can be operated at a lower temperature, which is suitable for the deposition of flexible substrates.
[0132] Chemical vapor deposition (CVD): Graphene and other materials are deposited layer by layer on a substrate to form a composite structure through chemical vapor deposition. CVD is suitable for preparing high-quality graphene films and has good controllability.
[0133] Spray drying method: A solution containing graphene and LDH precursor is deposited on a substrate by spray drying to gradually form a multilayer composite structure. This method is suitable for mass production and has low cost.
[0134] Next, after forming a multilayer LDH-graphene composite film by a layer-by-layer deposition method, a hot pressing process is required to perform a lamination step to firmly combine the layers to form a final complete composite film of the chloride ion barrier layer 2 on the base layer.
[0135] The hot pressing temperature has a great influence on the bonding strength of each layer of material and the overall density of the film. If the temperature is too low, the interlayer bonding is insufficient, resulting in poor mechanical strength and durability of the film; if the temperature is too high, it may cause thermal degradation of the material, especially the structure of the graphene layer and LDH may be destroyed, affecting its conductivity and barrier effect.
[0136] The hot pressing temperature is set at 100°C-150°C, which is selected according to the thermal stability of the material and the bonding requirements. For the graphene and LDH composite film structure in the present invention, this temperature range can ensure the effective bonding of each layer of material and avoid thermal degradation of the material.
[0137] The pressure control of hot pressing is crucial for the close contact and bonding between the layers. Too low pressure may lead to loose bonding between the layers, resulting in bubbles or gaps, affecting the conductivity and chloride ion barrier effect of the film; too high pressure may lead to uneven film thickness or material deformation.
[0138] The hot pressing pressure was set between 5-10 MPa to ensure adequate bonding between the membrane layers without destroying the structural integrity of the membrane.
[0139] The hot pressing time determines the efficiency of the lamination process and the adequacy of the material bonding. If the time is too short, the lamination will be incomplete, the bonding between the layers will not be strong, and the mechanical properties of the composite film will be affected; if the time is too long, it may cause aging or structural changes of the material.
[0140] The heat pressing time is controlled between 5-15 minutes, and the specific time is adjusted according to the thickness of the film and the number of layers. Thicker multi-layer structures require longer time to ensure full bonding during the heat pressing process.
[0141] As an embodiment of the present invention, during the hot pressing process, a protective layer 3 may be formed on the surface of the multilayer LDH-graphene composite film formed by the layer-by-layer deposition method, and the material of the protective layer 3 may be, for example, PET material, PE material, etc., and the thickness of the protective layer 3 may be 30-50 nm. In actual use, the protective layer 3 may be torn off.
[0142] After the hot pressing process, the graphene composite heating film with chloride ion barrier capability of the present invention is formed, wherein the thickness of the graphene heating layer 1 is 50-500nm, and the thickness of the chloride ion barrier layer 2 is 100-1000nm. The prepared composite film can be cut into corresponding shapes and sizes according to the size requirements of actual applications.
[0143] Specifically, the graphene composite heating film of the present invention has the following advantages:
[0144] (1) Multifunctional (heating function and shielding function):
[0145] In the graphene composite heating film of the present invention, LDH not only acts as a chloride ion barrier in the chloride ion barrier layer 2, but also has the characteristics of ion regulation, high thermal stability, and adjustable conductivity. The graphene heating layer 1 ensures efficient electric heating performance due to its excellent conductivity and thermal conductivity. Compared with other graphene composite materials with a single function, the present invention achieves multifunctionality. It can be used as a heating film and can shield chloride ions, so that it can maintain good performance for a long time in a corrosive environment. This is particularly competitive in fields such as marine environment and building protection that require a combination of corrosion resistance and heating functions.
[0146] (2) Structural stability:
[0147] Existing composite membrane materials, such as conductive polymers or certain nanomaterials, have poor structural stability under extreme conditions and are prone to degradation or failure; the LDH+graphene composite membrane of the present invention has significant advantages in this regard and can maintain a stable heating effect for a long time, especially in harsh working environments; the layered structure and stability of the LDH of the present invention perform well under high temperature or chemical corrosion conditions; compared with certain materials that are easily decomposed under high temperature or acid-base conditions, the combination of LDH and graphene is more stable in structure.
[0148] (3) Good mechanical strength and flexibility:
[0149] The existing graphene composite films are difficult to maintain good performance under bending or external force due to the brittleness of the substrate or insufficient mechanical strength. The present invention enhances the mechanical properties of the composite film by introducing LDH, which is particularly suitable for flexible electronic devices and heating equipment. The layered structure of the LDH of the present invention provides additional mechanical strength, and the graphene gives the composite film good flexibility. The combination of the two enables the composite film of the present invention to not only withstand external stress, but also have good bending performance.
[0150] (4) Highly efficient heating:
[0151] Graphene has excellent electrical conductivity and can achieve rapid heating at a relatively low voltage. The composite film of the present invention can not only provide a uniform heating effect, but also can work stably in high humidity and high salinity environments, and is suitable for use in harsh environments such as the ocean and chemical industry.
[0152] (5) High temperature stability:
[0153] The composite membrane of the present invention exhibits excellent stability in a high temperature environment and is not prone to performance degradation, which enables it to be used in a high temperature environment for a long time to ensure continuous and efficient operation of the system.
[0154] (6) Environmentally friendly and controllable:
[0155] Compared with other material systems, such as certain metal-based or organic polymer-based composite membranes, the LDH+graphene composite membrane of the present invention is more environmentally friendly and has adjustable performance; by simply adjusting the LDH composition (for example, inserting different anions between LDH layers), the functional requirements in different application scenarios can be achieved without introducing harmful chemicals; LDH is a green, non-toxic material with an environmentally friendly preparation process, and by adjusting the type and proportion of metal ions in LDH, the physical and chemical properties of the composite membrane, such as electrical conductivity and thermal conductivity, can be flexibly controlled.
[0156] (7) Environmental adaptability:
[0157] In addition to the chloride ion blocking capability, the LDH+graphene composite film of the present invention can maintain stable performance in a variety of harsh chemical environments. The composite film can not only block chloride ions, but also block the penetration of moisture and other corrosive liquids, meeting the use requirements in humid environments.
[0158] (8) Economical:
[0159] The preparation process of graphene materials has gradually matured. Coupled with the controllability of the composite film preparation process and the low cost of materials, this heating film can be mass-produced more economically. The preparation process of the composite film is compatible with existing coating, lamination and other processes, and can be easily integrated into existing production lines, reducing production costs and time.
[0160] The graphene composite heating film with chloride ion blocking ability prepared by the present invention, by introducing layered double hydroxide (LDH), not only acts as a chloride ion barrier in the composite film, but also has the characteristics of ion regulation, high thermal stability, adjustable conductivity, etc., and also provides additional mechanical strength. At the same time, graphene gives the composite film good flexibility as well as excellent electrical conductivity and thermal conductivity, ensuring efficient electric heating performance. The combination of the two enhances the mechanical properties of the composite film, which can be used as a heating film and can shield chloride ions, so that it can maintain good performance for a long time in a corrosive environment. It is particularly suitable for areas that require efficient blocking of chloride ion corrosion and serve in cold environments, such as marine equipment, chemical equipment, and building structures.
[0161] Based on this, the present invention further provides an application of the graphene composite heating film with chloride ion barrier capability as described above in the preparation of ice and snow melting materials.
[0162] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.
[0163] Application Example 1: Marine Engineering
[0164] Application background: In the marine environment, equipment and structures are exposed to seawater containing chloride ions for a long time, which is prone to chemical corrosion and causes structural damage.
[0165] ① Bathroom equipment on the ocean platform:
[0166] Application background: Bathroom facilities on offshore platforms are often exposed to moisture, salt spray and high-salt environments, and are prone to corrosion.
[0167] Heating film function: The graphene composite heating film of the present invention is installed on the metal shell and bracket of the bathroom equipment to prevent ice and moisture accumulation through heating. At the same time, the LDH layer effectively blocks chloride ions and reduces the impact of corrosion on the metal structure.
[0168] Film thickness: 10-15μm.
[0169] Heating temperature: 40-60℃, ensuring a warm and comfortable environment.
[0170] Chloride ion blocking rate: >96%, which can significantly extend the service life of the equipment.
[0171] ② Heating protection of submarine cable sheath:
[0172] Application background: Submarine cables are immersed in seawater containing chloride ions for a long time, which can easily lead to damage of cable sheath due to corrosion.
[0173] Function of the heating film: The graphene composite heating film of the present invention is coated on the outside of the cable to prevent the outer layer of the sheath from freezing through continuous heating, while blocking the entry of chloride ions to protect the internal structure of the cable.
[0174] Film thickness: 15-20μm.
[0175] Heating temperature: 50-70℃, ensuring the cable works normally in cold environment.
[0176] Chloride ion blocking rate: >98%.
[0177] ③Ship hull protection:
[0178] Application background: The hull of a ship is in contact with seawater for a long time, especially when moored, and is very susceptible to chloride ion corrosion.
[0179] Heating film function: The graphene composite heating film covering the ship's hull can not only prevent the seawater from freezing by heating, but also reduce the corrosion of the metal hull by chloride ions in the seawater.
[0180] Film thickness: 20-30μm.
[0181] Heating temperature: 45-65℃.
[0182] Chloride ion blocking rate: >97%, effectively extending the service life of the ship's hull.
[0183] In summary, the graphene composite heating film with chloride ion barrier capability of the present invention is applied to the surface of structures such as offshore platforms, submarine cables and ship hulls, which can not only prevent ice formation through the heating function, but also effectively block the short-term chloride ions and extend the service life of the structure.
[0184] Application Example 2: Concrete Structure
[0185] Application background: In concrete structures such as bridges, tunnels and building foundations, chloride ion penetration can cause corrosion and rust, affecting the safety of the structure.
[0186] ① Protection of bridge concrete structure:
[0187] Application background: The bridge surface is exposed to the atmosphere and chloride ion-containing environment for a long time, which is prone to corrosion. Especially under the frequent freeze-thaw cycles in winter, the bridge surface cracks and the steel bar corrosion is aggravated.
[0188] Heating film function: The graphene composite heating film of the present invention is embedded in the concrete layer of the bridge to keep the surface temperature of the concrete stable by heating, thus preventing surface damage caused by freeze-thaw cycles. At the same time, the LDH layer can block the penetration of chloride ions and prevent steel bar corrosion.
[0189] Film thickness: 10-20μm.
[0190] Heating temperature: 40-60℃, ensuring stable surface temperature in low temperature environment in winter.
[0191] Chloride ion blocking rate: >95%, greatly reducing the risk of corrosion of steel bars inside concrete.
[0192] ②Tunnel lining anti-corrosion:
[0193] Application background: The concrete lining of the tunnel is easily corroded by chloride ions in a humid environment, resulting in a decrease in structural strength, especially in coastal tunnels.
[0194] Heating film function: The graphene composite heating film of the present invention is embedded in the tunnel concrete lining to keep the lining dry by heating, avoiding corrosion caused by the combination of moisture and chloride ions. The LDH layer in the film can effectively prevent the penetration of chloride ions and extend the service life of the tunnel.
[0195] Film thickness: 15-25μm.
[0196] Heating temperature: 50-70℃.
[0197] Chloride ion blocking rate: >97%.
[0198] ③Building foundation protection:
[0199] Application background: Underground building structures such as foundations and basements are exposed to high humidity environments for a long time. Chloride ions can easily penetrate through groundwater, causing corrosion of steel bars in concrete.
[0200] Heating film function: The graphene composite heating film of the present invention is embedded in the concrete of the building foundation to keep the foundation part dry by heating, and prevent chloride ions from entering the concrete through moisture. The LDH layer can serve as an effective barrier to prevent chloride ions from entering the surface of the steel bars.
[0201] Film thickness: 15-30μm.
[0202] Heating temperature: 45-60℃.
[0203] Chloride ion blocking rate: >96%.
[0204] Summary: The graphene composite heating film of the present invention is embedded in concrete as an intelligent protection system. The heating function of the film can maintain the surface temperature of the concrete, prevent damage caused by freeze-thaw cycles, and hinder the penetration of chloride ions into the steel bars, thereby effectively protecting the structure.
[0205] Application Example 3: Automobile Antifreeze and Protection System
[0206] Application background: Automobiles and other cold areas often need to conduct investigations on ice, snow and chlorine salts, which will cause corrosion of the vehicle body and aging of components.
[0207] ① Windshield de-icing system:
[0208] Application background: In cold regions, car windshields are easily covered with snow and frost, which affects the driver's vision. Traditional defrosting systems are time-consuming and not efficient enough.
[0209] Heating film function: Embedding graphene composite heating film on the windshield can quickly heat and melt ice and snow. The film can also effectively block the erosion of chloride salts and prevent the metal frame at the edge of the glass from rusting.
[0210] Film thickness: 5-10μm.
[0211] Heating temperature: 50-70℃, ensuring fast ice and snow removal.
[0212] Chloride ion blocking rate:>95%.
[0213] ② Vehicle structure protection system:
[0214] Application background: Vehicle bodies are often exposed to salt-containing ice and snow melting agents in winter. Long-term exposure to this environment will cause corrosion of the metal structure of the vehicle body.
[0215] Heating film function: The graphene composite heating film of the present invention is applied to the chassis and external metal panels of the vehicle body. It prevents ice and snow accumulation by heating, blocks chloride salts, reduces metal corrosion caused by snow melting agents, and extends the life of the vehicle body.
[0216] Film thickness: 10-20μm.
[0217] Heating temperature: 40-60℃, to ensure that the vehicle surface remains free of ice and snow.
[0218] Chloride ion blocking rate: >97%.
[0219] ③Tire protection and heating system:
[0220] Application background: When vehicle tires are driving on ice-covered roads, they are easily damaged by road salt and snow-melting agents, which can cause tire rubber aging and wheel corrosion.
[0221] Heating film function: The graphene composite heating film of the present invention is embedded in the tire to melt the ice and snow attached to the tire by heating, and to block chloride ions from entering the tire, thereby reducing tire aging and wheel hub corrosion.
[0222] Film thickness: 5-8μm.
[0223] Heating temperature: 35-50℃, to ensure rapid melting of ice and snow.
[0224] Chloride ion blocking rate: >96%.
[0225] In summary, the graphene composite heating film of the present invention is applied to automobile windshields, body structures or tires to remove ice and snow by heating, and its chloride ion barrier function can prevent corrosion caused by chloride salts and improve the corrosion resistance of the vehicle.
[0226] Application Example 4: Fixed Heating System for Pipelines and Tanks
[0227] Application background: Pipelines and storage tanks in the fields of petroleum, natural gas, and chemical industry handle media containing chloride ions all year round and are prone to corrosion.
[0228] ①Oil pipeline protection:
[0229] Application background: Oil pipelines transport crude oil containing chloride ions for a long time, and the inner wall of the pipeline is prone to corrosion, especially in cold environments, where the risk of crude oil solidification increases.
[0230] Film thickness: 20-30μm.
[0231] Heating temperature: 50-80℃, suitable for oil transportation in extremely low temperature environment.
[0232] Chloride ion blocking rate: >98%.
[0233] Heating film function: The graphene composite heating film of the present invention is covered on the inner wall of the pipeline to ensure that the crude oil remains fluid and prevents low-temperature solidification by heating. At the same time, the LDH layer effectively blocks the corrosion of chloride ions on the pipeline metal and prolongs the service life of the pipeline.
[0234] ②Natural gas storage tank protection:
[0235] Application background: Natural gas storage tanks are exposed to high humidity and chloride ion-containing environments, and the outer walls of the tanks are susceptible to corrosion, affecting their structural strength and safety.
[0236] Heating film function: The graphene composite heating film of the present invention is covered on the surface of the storage tank to keep the outer wall of the storage tank dry and prevent the penetration of chloride ions through the LDH layer. The heating function can maintain a certain temperature to avoid coagulation or insufficient gasification of the medium.
[0237] Film thickness: 15-25μm.
[0238] Heating temperature: 45-65℃, suitable for natural gas storage environment.
[0239] Chloride ion blocking rate:>95%.
[0240] ③Chemical pipeline anti-corrosion and anti-freezing:
[0241] Application background: Chemical pipelines are often used to transport chemical media containing chlorides. Especially in low-temperature environments, the media may solidify, causing pipeline blockage or rupture.
[0242] Heating film function: The graphene composite heating film of the present invention is used on the surface or inner wall of a chemical pipeline to maintain the fluidity of the medium through heating, and to block the penetration of chloride ions, thereby preventing the pipeline from failing due to chemical corrosion.
[0243] Film thickness: 10-20μm.
[0244] Heating temperature: 40-70℃, ensuring the stability of chemical media and pipeline safety.
[0245] Chloride ion blocking rate: >96%.
[0246] In summary, the graphene composite heating film of the present invention is covered on the inner wall of the pipeline or the surface of the storage tank, which prevents the medium from solidifying through the heating function and hinders the penetration of chlorine isolators, thereby extending the service life of the pipeline and the storage tank.
[0247] Application Example 5: Heating and Anti-corrosion System of Intelligent Building
[0248] Application background: Modern intelligent buildings have higher requirements for energy conservation, environmental protection and structure, especially in cold areas, where heating and anti-corrosion measures such as exterior wall, roof and floor heating are extremely important.
[0249] ①Exterior wall heating and anti-corrosion system:
[0250] Application background: The exterior walls of buildings in cold areas are susceptible to low temperature and humidity, and are prone to heat loss and corrosion caused by chloride ions.
[0251] Heating film function: embedding the graphene composite heating film of the present invention in the exterior wall of a building can reduce heat loss and increase indoor temperature by heating in winter. The LDH layer can effectively block the intrusion of external chloride ions and prevent the wall structure from being corroded by moisture and salt erosion.
[0252] Film thickness: 10-15μm.
[0253] Heating temperature: 35-50℃, maintain suitable indoor temperature.
[0254] Chloride ion blocking rate: >96%.
[0255] ②Roof antifreeze and insulation system:
[0256] Application background: Roofs are exposed to wind, snow and salt spray environments and are easily damaged by low-temperature freeze-thaw cycles, especially in coastal areas, where chloride ion erosion is more serious.
[0257] Heating film function: Embedding the graphene composite heating film of the present invention in the roof structure can prevent the formation of snow and ice in winter and reduce heat loss by heat preservation. The LDH layer in the film can prevent the penetration of chloride ions and prevent the corrosion of roof materials.
[0258] Film thickness: 15-20μm.
[0259] Heating temperature: 40-60℃, ensuring rapid melting of snow in winter.
[0260] Chloride ion blocking rate:>95%.
[0261] ③ Floor heating and moisture-proof system:
[0262] Application background: In the floor structure of smart buildings, especially in basements or humid areas, moisture and salt may penetrate into the floor, affecting the safety and comfort of the building structure.
[0263] Heating film function: The graphene composite heating film of the present invention is laid under the floor to provide stable floor heating and improve indoor comfort. The LDH layer can block the entry of surface moisture and chloride ions to prevent corrosion of structural materials under the floor.
[0264] Film thickness: 8-12μm.
[0265] Heating temperature: 30-45℃, providing comfortable floor heating effect.
[0266] Chloride ion blocking rate: >97%.
[0267] In summary, embedding the graphene composite heating film of the present invention in the exterior wall, roof or floor of a building can provide effective heating in winter, while preventing corrosion of the building structure by blocking chloride ions, thereby improving the durability and comfort of the building.
[0268] Application Example 6: Road and Bridge Snow Melting, Deicing, Heating and Anti-corrosion System
[0269] Application background: Heilongjiang Province is located in northeast China. It has long and cold winters and often faces the challenge of large-scale snow and ice. In order to ensure traffic safety, chloride salts (such as sodium chloride and calcium chloride) are usually used to melt snow and de-ice roads and bridges. However, although chloride salts can effectively melt snow, they can also cause serious corrosion to the reinforced concrete structure of bridges, shorten the service life of bridges, and increase maintenance costs.
[0270] Film thickness: 20-30 μm (graphene layer 10-15 μm, LDH layer 10-15 μm).
[0271] Heating temperature: 40-60℃, can keep the surface of the structure dry and inhibit corrosion.
[0272] Chloride ion blocking rate: >97%, effectively preventing the corrosion of chloride ions in seawater or deicing salt.
[0273] Power density: 15-20W / m 2 , ensuring continuous heating effect in extreme weather.
[0274] Summary: The graphene composite heating film of the present invention is laid on the surface of the bridge, and automatic heating and temperature regulation are achieved through embedded sensors and intelligent control systems. During the entire winter operation, the high thermal conductivity of the graphene layer of the graphene composite heating film of the present invention enables the system to reach the required temperature in a short time, reducing energy consumption, and the LDH layer effectively blocks chloride ion corrosion. The service life of the bridge is expected to be extended by 5-10 years, reducing maintenance costs. At the same time, the system effectively prevents ice from forming on the bridge surface and greatly reduces the corrosion of chloride salts to the bridge structure.
[0275] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A graphene composite heating film with chloride ion barrier capability, characterized in that: It comprises a graphene heating layer and a chloride ion barrier layer. The chloride ion barrier layer is a multi-layer composite structure. Each layer of the composite structure is composed of alternating layers consisting of layered double metal hydroxides (LDH) and graphene layers intercalated between the layered double metal hydroxides (LDH).
2. The graphene composite heating film with chloride ion barrier capability according to claim 1, characterized in that: The layered double metal hydroxide (LDH) is selected from one or more of magnesium aluminum layered double metal hydroxide, zinc aluminum layered double metal hydroxide, cobalt aluminum layered double metal hydroxide, nickel aluminum layered double metal hydroxide, titanium aluminum layered double metal hydroxide, zinc iron layered double metal hydroxide and copper aluminum layered double metal hydroxide, preferably magnesium aluminum layered double metal hydroxide.
3. The graphene composite heating film with chloride ion barrier capability according to claim 1 or 2, characterized in that: In the interlayer structure of the layered double hydroxide (LDH), anionic carbonate ions (CO3 2- ) and / or sulfate ions (SO4 2- ).
4. The graphene composite heating film with chloride ion barrier capability according to claim 2, characterized in that: The molar ratio of metal ions in the layered double hydroxide (LDH) is 2+ / M 3+ =(1-5):1, preferably 2:1 or 3:
1.
5. The graphene composite heating film with chloride ion barrier capability according to claim 1, characterized in that: The material of the graphene heating layer is modified graphene, preferably chemically reduced modified graphene oxide (rGO).
6. The graphene composite heating film with chloride ion barrier capability according to claim 1, characterized in that: The thickness of the graphene heating layer is 50-500 nm, and the thickness of the chloride ion barrier layer is 100-1000 nm.
7. A method for preparing a graphene composite heating film having chloride ion barrier capability as claimed in any one of claims 1 to 6, characterized in that: The steps include: Modifying the graphene heating layer of the substrate layer to form a graphene heating layer; Preparation of layered double hydroxides (LDH) and LDH-graphene composites having graphene layers intercalated between the layered double hydroxides (LDH); forming a multilayer LDH-graphene composite film as a chloride ion barrier layer on the substrate layer of the modified graphene heating layer; Hot pressing is performed to form a graphene composite heating film with chloride ion barrier capability.
8. The preparation method according to claim 7, characterized in that: The LDH-graphene composite material is prepared by a solution coprecipitation method. During the coprecipitation reaction, the pH value of the reaction solution is between 8.5 and 10.5, and the reaction temperature is within the range of 25° C. to 80° C.; wherein, in the formed LDH-graphene composite material, an alternating layer structure consisting of a layered double metal hydroxide (LDH) and graphene layers intercalated between the layered double metal hydroxides (LDH) is formed, and the total number of layers is between 10 and 100 layers. The thickness ratio of LDH to the graphene layer is (1-5):1, preferably (1-2):
1.
9. The preparation method according to claim 7, characterized in that: In the step of forming a multilayer LDH-graphene composite material on the base layer of the modified graphene heating layer, the LDH-graphene composite material is uniformly coated on the graphene heating layer by a coating method, a solution impregnation method, a layer-by-layer assembly method, a sol-gel method, a chemical vapor deposition method (CVD) or a spray drying method, and a multilayer composite layer composed of the LDH-graphene composite material is formed on the graphene heating layer.
10. Use of a graphene composite heating film with chloride ion barrier capability as described in any one of claims 1 to 6 and a graphene composite heating film with chloride ion barrier capability prepared by the preparation method as described in any one of claims 7 to 9 in preparing ice and snow melting materials.